2017
DOI: 10.1104/pp.16.01844
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Stomatal Density in Barley Improves Drought Tolerance without Impacting on Yield

Abstract: The epidermal patterning factor (EPF) family of secreted signaling peptides regulate the frequency of stomatal development in model dicot and basal land plant species. Here, we identify and manipulate the expression of a barley (Hordeum vulgare) ortholog and demonstrate that when overexpressed HvEPF1 limits entry to, and progression through, the stomatal development pathway. Despite substantial reductions in leaf gas exchange, barley plants with significantly reduced stomatal density show no reductions in grai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
288
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 304 publications
(304 citation statements)
references
References 48 publications
12
288
2
2
Order By: Relevance
“…Additionally, Yang et al () confirmed that the expression of many Arabidopsis genes involved in wax formation was intensified after the induction of the SHN1 gene, whereas the expression of selected genes involved in stomatal development decreased. Moreover, a recent report by Hughes et al () on the overexpression of HvEPF1 , encoding a peptide suppressing stomatal development in barley, demonstrated that the reduced stomatal density substantially improved plant drought tolerance without negative effects on yields in pot‐grown plants under glasshouse conditions, similarly to our findings in wheat. In this study, we analysed the expression of three wheat orthologues of the barley gene encoding HvEPF1 that correspond to homologues of wheat genomes A, B, and D and the wheat orthologue of the Arabidopsis MUTE gene encoding bHLH TF (Figures S8 and S9).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Additionally, Yang et al () confirmed that the expression of many Arabidopsis genes involved in wax formation was intensified after the induction of the SHN1 gene, whereas the expression of selected genes involved in stomatal development decreased. Moreover, a recent report by Hughes et al () on the overexpression of HvEPF1 , encoding a peptide suppressing stomatal development in barley, demonstrated that the reduced stomatal density substantially improved plant drought tolerance without negative effects on yields in pot‐grown plants under glasshouse conditions, similarly to our findings in wheat. In this study, we analysed the expression of three wheat orthologues of the barley gene encoding HvEPF1 that correspond to homologues of wheat genomes A, B, and D and the wheat orthologue of the Arabidopsis MUTE gene encoding bHLH TF (Figures S8 and S9).…”
Section: Discussionsupporting
confidence: 89%
“…To investigate the influence of the constitutive TaSHN1 overexpression on stomatal complex pathway genes, we analysed the expression of wheat homologues of two genes encoding key stomatal regulators EPF1 (Franks, Doheny‐Adams, Britton‐Harper, & Gray, ; Hara, Kajita, Torii, Bergmann, & Kakimoto, ) and bHLH TF (Qi et al, ). We identified three wheat homologues of EPF1 in the NCBI database using the corresponding barley protein sequence as a query (Hughes et al, ). The alignment of three allelic variants of EPF1, originating from wheat A, B, and D genomes, with the barley protein sequence (Figure S8a) indicates high conservation.…”
Section: Resultsmentioning
confidence: 99%
“…To simulate future conditions, we conducted experiments at an elevated 450–480 ppm CO 2 concentration. As reported previously in barley (Hughes et al ., ), overexpression of OsEPF1 in rice led to arrested stomatal development, resulting in reductions in stomatal density, stomatal index and, in some cases, stomatal size. Both in rice and barley, these phenotypic changes at the leaf surface led to increased drought tolerance by restricting water loss, both when water was plentiful and under drought conditions.…”
Section: Discussionmentioning
confidence: 94%
“…The Update review by Chater et al (2017) touches on some of the most recent developments on this topic. As an example of how this knowledge may be applied, again we point the reader to the research article by Hughes et al (2017). de Marcos et al (2017) uncover an unexpected interaction between brassinosteroid signaling and transcriptional control behind cell fates leading to stomatal development.…”
mentioning
confidence: 92%
“…The Update reviews of Vialet-Chabrand et al (2017b) and Matthews et al (2017) address the potential for improved water use efficiencies by enhancing the kinetics of guard cell responses to environmental cues relevant for photosynthesis. Hughes et al (2017) demonstrate the efficacy of manipulating stomatal densities to enhance water use efficiency and drought tolerance, while Hochberg et al (2017) highlight the interplay between stomatal function, water delivery to the leaf, and leaf shedding in the field.…”
mentioning
confidence: 99%